Inclusive Learning Strategies for Students with Visual Impairments: A Culture-Based Audio-Kinesthetic Case Study - Erik Aditia Ismaya; Sugoro Bhakti Sutono (AL-ISHLAH: Jurnal Pendidikan, 2025)
Learners with visual impairments face significant challenges due to the prevalence of visually based instructional methods. Inclusive education necessitates the utilization of multisensory and culturally responsive strategies to overcome these barriers. This study explores the effectiveness of local culture-based audio-kinesthetic learning media in enhancing engagement and concept understanding among visually impaired individuals. This qualitative case study was conducted at the Pendowo Social Service Center for Sensory Disabilities in Kudus Regency, Indonesia. A total of 30 visually impaired participants (12 female, 18 male), along with 2 caregivers and 3 therapists, were involved. Data were collected through participatory observation, semi-structured interviews, and documentation, and analyzed thematically using a naturalistic inquiry framework. Findings indicate that integrating audio-kinesthetic media with local cultural elements—such as folklore, gamelan rhythms, and kinesthetic simulations—significantly improved learning participation, motivation, and comprehension. Observations showed that 87% of participants actively engaged with learning activities. Cultural stimuli increased emotional connection and memory retention, with up to 42% improvement in post-session concept recall. The study demonstrates that combining multisensory strategies with culturally relevant content enhances both cognitive and emotional learning outcomes. Local culture-based audio-kinesthetic media fostered a stronger sense of identity, inclusion, and social engagement among participants.